PERILAKU ANALISIS ASPHALT CONCRETE WEARING COARSE (AC-WC) POROUS DENGAN BAHAN TAMBAH SERAT BAJA DAN RUBBER - Surasa Waluya; Rachmat Mudiyono; Juny Andry Sulistyo (Pondasi, 2025)
In Indonesia, roads often experience water accumulation during rain, leading to slippery conditions and an increased risk of accidents. To address this issue, porous asphalt has been developed using coarse aggregates and low sand content, allowing water to permeate both vertically and horizontally. This technology offers advantages such as improved skid resistance, reduced noise, and enhanced drainage functions, which help mitigate hydroplaning risks and maintain hydrological balance. This study utilized floodwater from Jl. Barito, Semarang Timur, aggregates from AMP PT. Perwita Karya, and JAP-57 polymer asphalt. The addition of LDPE plastic and varying amounts of steel fiber and rubber aimed to enhance the mixture's strength. The results indicated that the addition of rubber and steel fiber influenced the VIM (Void in Mix) value, where higher content reduced VIM and improved the mixture's ability to allow water to pass through.